Why we can't have nice things : social media's influence on fashion, ethics, and property - Phạm, Minh-Hà T., 1973- (Duke University Press, 2022)
"In Why We Can't Have Nice Things, Minh-Ha T. Pham provides a critical discussion of social media's unacknowledged importance to the development of global fashion. In particular, Pham examines the informal and extralegal work social media users do to monitor and regulate the fashion market against an array of "fake" fashion. Practices of "crowdsourced IP regulation" are undertaken in the name of ethical fashion but as Why We Can't Have Nice Things demonstrates, too often, this work relies on and reinforces racist and neocolonial norms, stereotypes, and capitalist logics about what counts as creativity and what counts as copying. The book explains how and why social media is now pivotal to the production and unequal distribution of fashion ethics, property, and value."--